Pottery Classification, Typology and Chronology at Tepe Yalfan, Hamedan - Tayebeh Almasi; Kazem Mollazadeh; Abbas Motarjem (Iranian Journal of Archaeological Studies, 2017)
Tepe Yalfan is one of the Iron Age III sites at the southeast of Hamedan, at the junction of the Simin and Yalfan rivers. This site was excavated in 2006 and 2007, in the frame of the activities related to the construction of Ekbatan Dam, and revealed remains of a mud-brick wall. Potsherd recovered from the excavation indicate an Iron Age III chronology for the site. Comprehensive studies on Iron Age III pottery have rarely been conducted; therefore, the present paper attempts to study classification, typology and chronology of the regional pottery to understand part of the pottery production during the Iron Age III. Typological studies of the pottery from Tepe Yalfan led to a classification into three types: buff, gray and cooking wares. These ceramics were compared to the ones from sites of the Iron Age III, including Nush-i Jan, Godin II, Baba JanII, Sialk VI, the cemetery B at Sialk, and Ozbaki IV. Based on comparative studies, one could date Yalfan to circa 800-600 BCE.